Ramadan Fasting and Anthropometric Parameters: The Role of MC4R rs17782313 Genotype in Adults Semarang, Indonesia - Kurniawan, Kezia Yunandra; Yocku, Monica Hermina Sharon Otline; Savitri, Rachmania Anggita; Haq, Arynal; Maharani, Nani; Fulyani, Faizah; Noer, Etika Ratna; Pramono, Adriyan (Journal of Biomedicine and Translational Research, 2026)
Background: The melanocortin-4 receptor (MC4R) gene regulates energy balance and food intake. The rs17782313 variant has been linked to altered homeostasis and eating behavior, and may also affect anthropometric and body composition responses during Ramadan fasting.Objective: To examine the effects of Ramadan fasting on anthropometric parameters, body composition, and macronutrient intake across different MC4R genotypes in adults.Methods: Thirty-five subjects were genotyped and grouped into recessive (TT, n=15) and dominant (TC+CC, n=20) allele carriers. Anthropometric and body composition measurements, dietary intake (SQ-FFQ), and physical activity (IPAQ-SF) were assessed before, during, and after Ramadan. Genetic data for rs17782313 were obtained from a prior investigation. Repeated Measures ANCOVA, adjusted for energy intake and physical activity, evaluated genotype and time effects.Results: The recessive group (TT) showed higher values than the dominant group (TC+CC), with significant differences in body weight, BMI, hip circumference, and visceral fat across all time points (p<0.05). Waist circumference differed significantly during and after Ramadan, while BMR differed only before fasting (p<0.05). Macronutrient intake and physical activity did not differ significantly, although protein and fat intake changes post-Ramadan were notable (p<0.05). A significant time–activity interaction was found for body weight (p=0.041). TT carriers experienced greater anthropometric benefits from Ramadan fasting compared to TC+CC carriers.Conclusion: Ramadan fasting significantly influences anthropometric parameters, body composition, and macronutrient intake across MC4R genotypes. Greater responses were observed in recessive carriers (TT), although fasting outcomes were also shaped by nutrition and physical activity. These findings highlight the interplay of genetic and environmental factors in energy regulation during Ramadan.